Complementary and alternative medicine/therapy for tobacco cessation in India: A secondary analysis of GATS-1 and 2 - Shivam Kapoor; Anushikha Dhankhar; Garima Bhatt; Sonu Goel; Rana J Singh (Indian Journal of Community Medicine, 2024)
Background: India has nearly 267 million adult tobacco users, with a slowly improving quitting rate. Among the many approaches to quitting the habit, such as counseling, nicotine replacement therapy, nicotine patch or gum, and prescribed allopathic medicines. Complementary and alternative medicine/therapy (CAM), a thousand-year-old practice in India, may also prove to be a potential method in tobacco cessation; however, there is scarce literature on the extent of use of CAM among tobacco users who attempt to quit the habit. Therefore, this study attempts to examine the potential of CAM as a strategy for tobacco control in India. Material and Methods: We undertook a secondary analysis of the data from both rounds of the Global Adult Tobacco Survey (GATS 2009 and 2016). The dependent variable included in the analysis was the use of traditional medicine as a method for quitting tobacco in three types of users—smokers, smokeless tobacco users, and dual users. The prevalence of CAM use was reported, and Chi-square test was applied to find the factors significantly associated with the use of CAM among tobacco users considering a P value of 0.05 to be statistically significant. Results: The overall prevalence of traditional medicine use for GATS-1 was observed to be more among dual users (4%), while for GATS-2, it was highest among smokers (3%). For both rounds of the GATS survey, the use of traditional medicine was found to be higher among males, rural residents, users with no education or less than primary education, and the eastern region. Conclusions: CAM has a promising potential for supporting tobacco cessation provided a concerted effort is undertaken to standardize pharmacopeia and establish robust clinical evidence. In addition, there is a need to create awareness, build the capacity of healthcare providers, and foster academic-industrial research in indigenous Ayurveda, Yoga, Naturopathy, Unani, Siddha, and Homeopathy (AYUSH) systems.